BUILT FOR GROWTH Expanding Your Business Around the Corner or Across the Globe - Rubinfeld, Arthur; Hemingway, Collins (Pearson, 2005)
If there's one thing that's consistent in today's business world, it's rapid change. So how do you not only stay steady but actually grow'and quickly enough to stay safely ahead of your competitors? Built for Growth delivers specific solutions to create a brand and presence that generates true customer passion, as you lay a solid foundation for long-term success. Author Arthur Rubinfeld was a major driver in Starbucks' unprecedented retail expansion from 100 stores to more than 4000-- and its transformation into one of the world's most recognized brands. Here he draws on his singular expertise to present a proven, holistic approach to conceiving, designing, and executing your business plan: creating exciting concepts, growing them to fruition in local markets, expanding rapidly, and keeping your brand fresh and relevant as it matures. His revolutionary approach to business strategy embodies strong personal values, promotes exceptional creativity, leverages scientific methodology in finance and market analysis, and brings it all together with 'old-time' customer service.